Web analytics with hands on projects in R - Shin, William; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2017)
"R is a popular choice of tool for analysts, offering a large variety of libraries pertaining to each and every task in data analysis. With practical projects based on various real-world domains and use-cases where web analytics can be used, this video will be your companion for implementing the various web analytics techniques using the free, open source libraries provided by R. This video will start by understanding the basics of web analytics, and why it is used in businesses worldwide. This will be followed by an introduction to R and its libraries, and understanding why R is a great choice for performing real-time analysis of your data. Analyse your website's traffic and understand customers' behaviour in real time, and use this information to optimize the performance of your website. You will also learn how to use the analytical capabilities of R to fully explore your Google Analytics Data and generate meaningful visualizations of your data using libraries like ggplot2 and generate reports based on various metrics and combinations. By the end of this tutorial, you will have a solid understanding of implementing the various web analytics techniques in R, and maximize your website's performance."--Resource description page.
Title from resource description page (viewed September 25, 2017).
Presenter, William Shin.
Keywords: Web applications -- Development; R (Computer program language); Web usage mining; Electronic books